Gambaran Tingkat Pengetahuan Perawat Dialisis Tentang Pencegahan TerjadinyaVenous Needle Dislodgement Pada Pasien Yang Menjalani Tindakan Hemodialisa - Nurrahman, Taufiq Budi, Agus Sudaryanto, S.Kep., Ns., M.Kes (2016)
ABSTRACT Hemodialysis treatment was a therapy but it had complicated symptom , (headaches, cramps), till serious complications such as Venous Needle Dislodgement (VND). VND happened when the venous fistula needle becames dislocated out of the vascular access,and could be in blood loss. VND which could cause heavy bleeding and even death. Therefore, nurses should be understood about VND. The purpose of this study was to described the level of nurses knowledge to prevention of VND in patients with hemodialysis therapy. This research used descriptive quantitative method that described the level of knowledge of nurses quantitatively. The sampling method used total sampling technique, the total sample that used were 51 nurses who served in the hemodialysis room. The conclusion was the level of nurses knowledge about the prevention of venous needle dislodgement was good enough. Where 12 nurses (23.5%) were in a good level, 30 nurses (58.8%) were in a goodenough level, 9 nurses (17.6%) are in a not-good-enaugh level. Therefore, for nurses should be increase knowledge about the management and prevention of venous needle dislodgement, in order to provide education and give counseling to patients to minimize the risk of fatal complications for the patient. Keywords : knowledge level, hemodialysis, dialysis nurses, prevention, venous needle dislodgement